Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Đỗ Thị Mai Lan
Xem chi tiết
Hoàng Phúc
5 tháng 12 2015 lúc 15:01

ta có:

(2x-4)^2>0

|y-5|>0

(x+y-z)^6>0

=>(2x-4)^2+|y-5|+(x+y-z)^6>0

mà theo đề:(2x-4)^2+|y-5|+(x+y-z)^6=0

=>(2x-4)^2=|y-5|=(x+y-z)^6=0

+)(2x-4)^2=0=>2x-4=0=>2x=4=>x=2

+)|y-5|=0=>y-5=0=>y=5

+)(x+y-z)^6=0=>x+y-z=0

thay x=2;y=5 vào x+y-z=0

=>2+5-z=0

=>7-z=0

=>z=7

vậy..

nhớ tick

MIRIKI NAKATA
Xem chi tiết
Nhọ Nồi
29 tháng 12 2015 lúc 17:06

x = 2

y = 5

z = -7

tam bay nhat tren doi
Xem chi tiết
Nguyễn Văn Cùi
Xem chi tiết
Nguyen Manh Cuong
Xem chi tiết
Nguyen Thi Bich Tram
Xem chi tiết
Huỳnh Ngọc Phương Uyên
Xem chi tiết
Li Ying
Xem chi tiết
Lê Việt
Xem chi tiết